Multicenter cohort study of patients with buried bumper syndrome treated endoscopically with a novel, dedicated device - Costa, Deborah; Despott, Edward J.; Lazaridis, Nikolaos; Woodward, Jeremy; Kohout, Pavel; Rath, Timo; Scovell, Louise; Gee, Ian; Hindryckx, Pieter; Forrest, Ewan; Hollywood, Coral; Hearing, Stephen; et al. (Gastrointestinal Endoscopy, 2021)
Background and Aims: Buried bumper syndrome (BBS) is a rare adverse event of percutaneous endoscopic gastrostomy (PEG) placement in which the internal bumper migrates through the stomal tract to become embedded within the gastric wall. Excessive tension between the internal and external bumpers, causing ischemic necrosis of the gastric wall, is believed to be the main etiologic factor. Several techniques for endoscopic management of BBS have been described using off-label devices. The Flamingo set is a novel, sphincterotome-like device specifically designed for BBS management. We aimed to evaluate the effectiveness of the Flamingo device in a large, homogeneous cohort of patients with BBS. Methods: A guidewire was inserted through the external access of the PEG tube into the gastric lumen. The Flamingo device was then introduced into the stomach over the guidewire. This dedicated tool can be flexed by 180 degrees, exposing a sphincterotome-like cutting wire, which is used to incise the overgrown tissue until the PEG bumper is exposed. A retrospective, international, multicenter cohort study was conducted on 54 patients between December 2016 and February 2019. Results: The buried bumper was successfully removed in 53 of 55 procedures (96.4%). The median time for the endoscopic removal of the buried bumper was 22 minutes (range, 5-60). Periprocedural endoscopic adverse events occurred in 7 procedures (12.7%) and were successfully managed endoscopically. A median follow-up of 150 days (range, 33-593) was performed in 29 patients (52.7%), during which no significant adverse events occurred. Conclusions: Through our experience, we found this dedicated novel device to be safe, quick, and effective for minimally invasive, endoscopic management of BBS.
CRIS-Team Scopus Importer:2021-02-12